2013
DOI: 10.1128/genomea.01030-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Elizabethkingia anophelis Strains R26 T and Ag1 from the Midgut of the Malaria Mosquito Anopheles gambiae

Abstract: Elizabethkingia anophelis is a species in the family Flavobacteriaceae. It is a dominant resident in the mosquito gut and also a human pathogen. We present the draft genome sequences of two strains of E. anophelis, R26T and Ag1, which were isolated from the midgut of the malaria mosquito Anopheles gambiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 14 publications
(13 reference statements)
0
32
0
Order By: Relevance
“…We found various antimicrobial resistance genes consistent with their resistance phenotypes, including metallo-β-lactamase ( bla GOB-1 and blaB14 in strain HKU36 and a novel bla GOB and blaB1 in strains HKU37 and HKU38) and extended-spectrum β-lactamase ( blaA CME-1 in strains HKU37 and HKU38 and a potential novel blaA CME-1 variant in strain HKU36). A comparison of these β-lactamases to their corresponding orthologs in E. meningoseptica genomes revealed only 74%–85% amino acid identities, indicating that E. anophelis and related bacteria are potential reservoirs of novel β-lactamase genes ( 19 , 34 , 35 ) . Other antimicrobial resistance genes found included multidrug-resistance efflux pumps (ATP binding cassette superfamily, major facilitator superfamily, resistance-nodulation-division families, multidrug and toxic-compound extrusion family) that potentially carry resistance to a variety of compounds; chloramphenicol acetyltransferase; aminoglycoside 6-adenyltransferase; and tetracycline resistant gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found various antimicrobial resistance genes consistent with their resistance phenotypes, including metallo-β-lactamase ( bla GOB-1 and blaB14 in strain HKU36 and a novel bla GOB and blaB1 in strains HKU37 and HKU38) and extended-spectrum β-lactamase ( blaA CME-1 in strains HKU37 and HKU38 and a potential novel blaA CME-1 variant in strain HKU36). A comparison of these β-lactamases to their corresponding orthologs in E. meningoseptica genomes revealed only 74%–85% amino acid identities, indicating that E. anophelis and related bacteria are potential reservoirs of novel β-lactamase genes ( 19 , 34 , 35 ) . Other antimicrobial resistance genes found included multidrug-resistance efflux pumps (ATP binding cassette superfamily, major facilitator superfamily, resistance-nodulation-division families, multidrug and toxic-compound extrusion family) that potentially carry resistance to a variety of compounds; chloramphenicol acetyltransferase; aminoglycoside 6-adenyltransferase; and tetracycline resistant gene.…”
Section: Resultsmentioning
confidence: 99%
“…E. anophelis strains R26 T and Ag1 were isolated from mosquitoes ( 35 ). Compared with those strains , the genomes of the 3 strains we identified possessed 33 unique hypothetical proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the genomes of several mosquito derived bacterial strains have been sequences, including Asaia sp., Elizabethkingia anophelis , Enterobacter sp., Pseudomonas sp., Serratia sp., Stenotrophomonas maltophila , and Staphylococcus hominis 55565758596061. These genome data allow one to analyse the microbial genetic repertoire that may be associated with symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous several studies have also reported a similar pattern of gut microbe enrichment (Tchioffo, Boissiere et al 2015;Muturi, Dunlap et al 2019), but nature of gutmicrobe interactions, especially microbial proteins facilitating blood meal digestion, remains poorly known (Chen, Blom et al 2017). Available draft genome sequence of cultured bacterial species predicts several metabolic pathways, but no functional relation has been established (Kukutla, Lindberg et al 2013;Pei, Hill-Clemons et al 2015).…”
Section: Fig 8 Relative Quantification Of Gut Immune Transcripts Inmentioning
confidence: 99%